Paralytic Ileus as a Rare Complication of Vincristine Therapy: A Case Report - Kumar, Keshavini Saravana; Balaji, Prithiha; Muppa, Leena (Indian Journal of Pharmacy Practice)
Paralytic ileus, a rare but serious complication of Vincristine therapy, is often underrecognized despite its potential to significantly impact patient outcomes. This case study describes a 68-year old woman who had non-Hodgkin's lymphoma and developed paralytic ileus after receiving R-CHOP treatment for the first time. Severe distension, nausea, constipation, and stomach discomfort were the patient's initial complaints. Dilated bowel loops without a mechanical blockage were discovered by diagnostic imaging. Nasogastric decompression, bowel rest, intravenous fluids, and supportive drugs were all part of the conservative therapy. The patient's condition improved with meticulous therapy, including the administration of metoclopramide and electrolyte correction, despite early hypokalemia and gastrointestinal distress. After 10 days, the patient's belly circumference shrank, her bowel movements came back, and she was ultimately released in stable condition. This case underscores the need for awareness of VCR-induced paralytic ileus and highlights the importance of early diagnosis and supportive care, including the use of prokinetic medications like metoclopramide to manage gastrointestinal motility issues. Preventive measures, such as prophylactic stool softeners, should be considered for patients undergoing VCR-based chemotherapy to mitigate the risk of this complication.
Keywords: Paralytic ileus; Vincristine; Metoclopramide; Chemotherapy; Adverse Drug Reaction; Chemotherapy toxicity